Periodically correlated random sequences spectral theory and practice - Hurd Harry L; Miamee Abolghassem (New Jersey John Wiley, 2007)
Early chapters of the book provide definitions, simple mathematics models, and simulations. The following five chapters give background on theory, beginning with a review of Hilbert space. The last three chapters treat issues of time series analysis for
Keywords: Correlation(Statistics); Sequences(Mathematics); Spectral theory(Mathematics); Stochastic processes